Analisis Pengaruh Reformasi Birokrasi Terhadap Kinerja Pegawai Pada Dinas Perhubungan Komunikasi dan Informatika Kabupaten Pandeglang - Bakhtiar, Rachmat (Desanta Publisher, 2023)
This research is a type of explanatory research, namely research that can be studied according to its level based on its objectives and objects. The population in this study were all employees in the Department of Transportation, Communication and Informatics, Pandeglang Regency, totaling 93 people. The analytical method used is descriptive and statistical analysis methods used simple linear regression tools, multiple, simultaneous significant testing and partial significant testing. Data is processed using SPSS 21.0 for windows. The data used are primary data and secondary data. This study used 93 respondents. Based on the results of the study, it can be seen simultaneously the value of Bureaucratic Reform from institutional/bureaucratic structuring (X1), management/management structuring (X2), HR/apparatus structuring (X3), Accountability (X4), public services (X5), has a significant effect on performance employee (Y) at the Department of Transportation, Communication and Informatics, Pandeglang Regency, with Fcount (3.566) > Ftable (2.481) and the results of partial testing (tcount) show that the institutional / bureaucratic arrangement variables (X1), management / management arrangements (X2), structuring of human resources/apparatus (X3), Accountability (X4), public services (X5)positive and significant effect on employee performance at the Department of Transportation, Communication and Informatics. Based on the results of the hypothesis test, it can be concluded that all X variables in this study have an influence on Y variables, which means that H0 is rejected and Ha is accepted.